2021
DOI: 10.21037/jtd-21-924
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features and prognostic value of epidermal growth factor receptor mutation in patients with pT1a and pT1b invasive lung adenocarcinoma after surgical resection

Abstract: Background: Previous studies have evaluated the prognostic value of epidermal growth factor receptor (EGFR) mutation in different subgroups of lung adenocarcinoma, but there remains controversial on this issue. We conduct this study aimed to reveal the prognostic value of EGFR mutation in patients with pT1a and pT1b invasive lung adenocarcinoma. Methods: From August 2009 to February 2015, 338 patients with pT1a and pT1b invasive lung adenocarcinoma who underwent EGFR mutation analysis were enrolled into this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In this analysis, no differences were reported in recurrence between patients with and without EGFR mutations. However, EGFR mutant patients showed prolonged overall survival in the entire cohort and in the analysis of the subgroups [16].…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 88%
“…In this analysis, no differences were reported in recurrence between patients with and without EGFR mutations. However, EGFR mutant patients showed prolonged overall survival in the entire cohort and in the analysis of the subgroups [16].…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 88%
“…The prognostic impact of EGFR alterations on early-stage NSCLC outcomes is conflicting, and factors associated with relapse risk in patients with EGFR -mutated NSCLCs need further elucidation. 23 , 24 In an Asian cohort, prognostic EGFR mutation impact on DFS for patients with pT1a and pT1b invasive lung non-squamous cancers after surgical resection did not differ from that of patients whose tumors expressed wild-type EGFR ; however, among all patients, OS was significantly longer for those with EGFR -mutated NSCLCs, and N0 and N1–2-stage subgroups. 21 That observation is probably explained by the number of effective targeted treatment options for metastatic EGFR -mutated NSCLCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognostic value of EGFR mutation is still controversial. Although most studies suggest that EGFR mutation is not a prognostic factor [14][15][16][17], and some studies believe that it is related to the low recurrence rate of stage I lung adenocarcinoma [14], STAS is a high-risk factor for poor prognosis of lung adenocarcinoma patients, and the prognosis of stage I patients with STAS is significantly worse [18][19][20]. Therefore, we retrospectively analyzed the clinical data of resected stage I lung adenocarcinoma patients with STAS, analyzed the relationship between clinical features and prognosis, and explored the influence of EGFR mutation status on the prognosis of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that EGFR mutation status can predict the prognosis of patients with lung adenocarcinoma [7][8][9][10][11]. On the contrary, some studies have claimed that EGFR mutation is not a risk factor for postoperative recurrence of lung adenocarcinoma [12][13][14]. In addition, most previous studies either did not consider the pathological stage of patients, or did not exclude the influence of histological subtypes, imaging features, EGFR-TKI treatment, and high-risk factors for recurrence [15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation